Seismic Performance Comparison of a High-Content SDA Frame and Standard RC Frame - John W. van de Lindt; R. Karthik Rechan (Advances in Civil Engineering)
This study presents the method and results of an experiment to study the seismic behavior of a concrete portal frame with fifty percent of its cement content replaced with a spray dryer ash (SDA). Based on multiple-shake-table tests, the high content SDA frame was found to perform as well as the standard concrete frame for two earthquakes exceeding design-level intensity earthquakes. Hence, from a purely seismic/structural standpoint, it may be possible to replace approximately fifty percent of cement in a concrete mix with SDA for the construction of structural members in high seismic zones. This would help significantly redirect spray dryer ash away from landfills, thus, providing a sustainable greener alternative to concrete that uses only Portland cement, or only a small percentage of SDA or fly ash.